Pengembangan E-Modul Berbasis Case Method pada Mata Kuliah Praktikum Konseling Psikodinamik - Probowati, Devy; Apriani, Rizka; Indreswari, Henny (citeus, 2025)
Guidance and counseling students as counselor candidates must have professional competence, one of which is counseling services. In order to facilitate this demand, the guidance and counseling department of the University Negeri Malang has a counseling practicum course that students must take. This study aims to develop a product as an interactive e-module based on a case method in the psychodynamic counseling practicum course. The development research method used was ADDIE (analysis, design, development, implementation, evaluation) which involved two tests of material and media experts and students as potential product users. The research instrument was a material validation questionnaire, media, and potential product users. Data analysis uses interrater-agreement. The results of this development research show that case-method-based e-module products have acceptability with very feasible criteria for accuracy, clarity, usability, convenience, and attractiveness to support learning in psychodynamic counseling practicum courses. Recommendations for further research are suggested to test the effectiveness of e-module products based on case methods in psychodynamic counseling practicum courses and to disseminate them to guidance and counseling students.